Utilization of Information Technology during the Covid-19 pandemic: Student's Perception of Online Lectures - Ubaedillah Ubaedillah; Damar Isti Pratiwi (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
The Covid-19 pandemic has a significant impact on higher education in Indonesia, including Muhadi Setiabudi University. Implementing the physical distancing policy then becomes the basis for implementing online lectures by utilizing information technology. This research was conducted to determine students' perceptions of using information technology in online learning at Muhadi Setiabudi University during the Covid-19 pandemic. The sample used in this study were all students of the University of Muhadi Setiabudi second semester and fourth semester of the Primary School Teacher Education Study Program, totalling 145 students. Which then uses Semi-structured Interviews as an instrument in the form of interviews with 20 students. The most widely used media in online lectures at Muhadi Setiabudi University are Google Classroom and WhatsApp group because this application is effortless to use. However, based on the survey results, it turns out that the implementation of online lectures has triggered Indonesian education's digital transformation. Various discourses, endorsing policies, and socialization regarding education in era 4.0 had previously failed. Covid-19, on the other hand, has had a significant effect on the digital transformation of education towards the generation of education 4.0.